Collaborative Economy: Market Design and Basic Regulatory Principles - Georgios Petropoulos (Intereconomics, 2017)
The rise of the collaborative economy platforms reveals that policymakers need to start thinking about how to introduce flexibility in the provision of services in these formal relationships with adequate protection for all of the involved parties.
Keywords: 330